2000
DOI: 10.1097/00000421-200004000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendroglioma: An Analysis of Prognostic Factors and Treatment Results

Abstract: This study, an analysis of variable prognostic factors affecting the treatment outcome for patients with oligodendroglioma, included a retrospective analysis of the medical charts of patients diagnosed with oligodendroglioma treated at our institution between 1975 and 1997. The endpoints analyzed were the progression-free survival (PFS), as well as the overall survival. The factors analyzed included extent of surgery, postoperative radiotherapy, pathologic grade, performance status, age, and sex. Of a total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Seizures from oligodendrogliomas may be generalized, simple partial, complex partial, or a combination. Other presenting symptoms have included headaches, mental status changes, vertigo, nausea, visual complaints, and/or localized weakness (1,5). Classically, it has been observed that patients with oligodendrogliomas often experience symptoms (usually seizures) for a number of years prior to their diagnosis, which was definitively made after an apoplectic event such as a peritumoral haemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Seizures from oligodendrogliomas may be generalized, simple partial, complex partial, or a combination. Other presenting symptoms have included headaches, mental status changes, vertigo, nausea, visual complaints, and/or localized weakness (1,5). Classically, it has been observed that patients with oligodendrogliomas often experience symptoms (usually seizures) for a number of years prior to their diagnosis, which was definitively made after an apoplectic event such as a peritumoral haemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…These tumors are further classified by subtypes and by histological grading as either low grade (WHO grade II) or anaplastic (WHO grade III). Grade of tumor appears to be the most significant prognosticator 1 .…”
Section: Discussionmentioning
confidence: 99%
“…1,31,60,70,75 Until highly accurate noninvasive histological assessment becomes a reality, surgery (biopsy sampling or resection) will continue to be essential for establishing an accurate diagnosis. 33,60 Tumor resection (when feasible) is also useful for reducing mass effect, which may be the cause of symptoms and/or neurological deficit.…”
Section: Surgical Interventionmentioning
confidence: 99%
“…9,12,34 Other favorable features include location in the frontal lobe (which may relate to the extent of resection possible) and higher initial or postoperative functional performance status. 1,22,45,71 Additional studies are currently underway in which the authors may be able to confirm the validity of these clinical prognostic factors (H Engelhard, et al, unpublished data).…”
Section: Clinical Prognostic Factors Andmentioning
confidence: 99%